2019
DOI: 10.1182/bloodadvances.2018024372
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of platelet function

Abstract: Although the hemostatic potential of adult platelets has been investigated extensively, regulation of platelet function during fetal life is less clear. Recent studies have provided increasing evidence for a developmental control of platelet function during fetal ontogeny. Fetal platelets feature distinct differences in reactive properties compared with adults. These differences very likely reflect a modified hemostatic and homeostatic environment in which platelet hyporeactivity contributes to prevent patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 132 publications
0
47
1
1
Order By: Relevance
“…The in vitro data reported in this study may therefore not faithfully represent the responses of which neonatal platelets are capable, especially given the well-established differences between neonatal and adult platelet phenotype and function. 53,54 Additional limitations of our study are that bleeding severity was assessed using only one definition of excessive bleeding and that the study included only a small number of patients. Future studies should be done to determine whether the findings reported herein are reproducible with other bleeding definitions (reviewed in Bercovitz et al 22 ) and whether they generalize to a larger, but equally well-characterized, group of neonatal cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro data reported in this study may therefore not faithfully represent the responses of which neonatal platelets are capable, especially given the well-established differences between neonatal and adult platelet phenotype and function. 53,54 Additional limitations of our study are that bleeding severity was assessed using only one definition of excessive bleeding and that the study included only a small number of patients. Future studies should be done to determine whether the findings reported herein are reproducible with other bleeding definitions (reviewed in Bercovitz et al 22 ) and whether they generalize to a larger, but equally well-characterized, group of neonatal cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…This observation might be caused by the fact that an increased inflammatory response induces more platelet adhesion in the microcirculation (12). Interestingly, also other factors, such as age (13)(14)(15), gender (16,17), and circadian rhythms (18,19), are known to affect platelet numbers and functions.…”
Section: Platelet Numbersmentioning
confidence: 99%
“…This is important, as significant changes in cerebral blood flow and cerebral artery pressure are associated with increased risk of intracranial bleeding in neonates [13]. d. There is a high likelihood of a developmental mismatch between transfused adult platelets and the immature neonatal hemostatic system [14].…”
Section: Paradigm Shiftmentioning
confidence: 99%